Methodology of the ZOC-BHVI High Myopia Cohort Study: The Onset and Progression of Myopic Pathologies and Associated Risk Factors in Highly Myopic Chinese. (2nd January 2018) - Chen, Yanxian; Xiao, Ou; Guo, Xinxing; Wang, Decai; Sankaridurg, Padmaja; Morgan, Ian; He, Mingguang
ABSTRACT: Purpose: The increasing prevalence of high myopia and its associated pathologies has raised challenges to ophthalmic services. This project aims to explore the onset and progression of myopic pathologies in highly myopic eyes through a prospective research cohort established in South China. Methods : Patients with high myopia (sphere ≤ −6.00 D) visiting the optometric clinic of Zhongshan Ophthalmic Center (ZOC) were invited to participate in the baseline examinations and follow-up visit over a 10-year period. People having secondary myopia, history of any refractive surgery, significant ocular media opacity, or other severe health problems were excluded. The measurements included visual acuity, ocular biometry, visual function, cycloplegic refraction, fundus imaging, ocular shape by MRI, blood tests and questionnaires. Results : A total of 890 participants completed the baseline examinations, with a mean age at baseline of 22.7 ± 12.4 years. The mean spherical equivalent at baseline was 10.13 ± 3.65 D, and the mean axial length (AL) was 27.52 ± 1.63 mm. The older subjects tended to have more severe myopia and longer ALs. Conclusion : The study will provide new knowledge on the relationship between high myopia and pathological changes such as myopic macular degeneration and staphyloma.